Fine‐scale cryogenic sampling of planktonic microbial communities: Application to toxic cyanobacterial blooms. (25th June 2016) - Puddick, Jonathan; Wood, Susanna A.; Hawes, Ian; Hamilton, David P.
Abstract: A lack of fine‐scale methods for sampling planktonic microbial populations hinders advancement in understanding the responses of these communities to environmental conditions. Current methods provide resolution at scales of centimeters to meters, but not at the millimeter‐scale required to understand highly stratified communities. To address this we developed two cryogenic sampling tools to collect spatially‐precise samples from aquatic environments while simultaneously preserving the microbial communities. The application of these samplers was examined over a 5.5 h period using a cyanobacterial scum ( Microcystis ) formed in experimental mesocosms. A cryogenic "surface snatcher" collected a discrete layer (ca. 1 mm) of surface water. Compared to conventional surface sampling methods, the surface snatcher samples contained up to 22‐times more microcystin, indicating that less underlying water was incorporated into the sample. A cryogenic "cold finger" sampler was used to collect vertical profiles of the upper 40 mm of the water column. This profiler provided new insights into the fine‐scale structure of Microcystis scums, demonstrating that more microcystin‐producing Microcystis was contained in the surface 5 mm than the 35 mm below. The results also showed that upregulation of microcystin production was highly localized in the top 2.5 mm of the Microcystis scum. Our results demonstrate that extreme changes in cyanobacterial communities can occur over small distances, and indicate that sampling resolution is of great importance for improving knowledge on cyanobacterial blooms and toxin production. While this study focused on microcystin‐producing Microcystis, the cryogenic sampling tools described here could be applied to any planktonic microbial community.